2006
DOI: 10.2746/042516406775374234
|View full text |Cite
|
Sign up to set email alerts
|

The complex blood supply to the equine testis as a cause of failure in laparoscopic castration

Abstract: Summary Reasons for performing study: Intra‐abdominal ligation/transection of the spermatic cord may result in necrosis of the testis; castration of abdominal cryptorchids via laparoscopy has therefore become common. Notwithstanding some adaptations of the technique, a small percentage of operations fail, prompting research into the anatomical background and clinical relevance of the procedure. Hypothesis: That an alternate blood supply may prevent complete necrosis of the testis after spermatic cord transec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 17 publications
3
38
0
Order By: Relevance
“…; Voermans et al . ). In our population, all horses but one castrated in this fashion were able to go back to work in less than a week, which is an economical consideration for horses in training.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Voermans et al . ). In our population, all horses but one castrated in this fashion were able to go back to work in less than a week, which is an economical consideration for horses in training.…”
Section: Discussionmentioning
confidence: 97%
“…Epididymis were preserved as described previously by Voermans et al . (). However, it is well recognised that androgens are not produced by the epididymis and therefore epididymal tissue cannot influence masculine behaviour (Cox et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it has subsequently been shown that the testis can revascularize and still produce testosterone [69, 70]. The testis has a complex blood supply that allows the testis to revascularize from vessels in the tunic, especially the cremaster vessels and the external pudendal artery [71]. …”
Section: Surgery Of the Male Reproductive Tractmentioning
confidence: 99%
“…This study has confirmed that the blood supply to the testicle may be preserved via the external pudendal artery when only the mesorchium is transected, as shown by Voermans et al . (). On reading the study by Voermans et al .…”
mentioning
confidence: 97%